Pengaruh Perputaran Kas dan Perputaran Piutang Terhadap Return On Assets Pada Perusahaan Sub Sektor Perhotelan yang Terdaftar di Bursa Efek Indonesia (Bei) Tahun 2016-2022 - Anindita, Intan Putri Puspa; Kusumawardhani, Aninditha Putri; Ningrum, Retno Widya; Putra, Okta Eka (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2024)
This study aims to determine the description and magnitude of the influence of the Effect of Cash Turnover and Receivables Turnover on Return On Assets in Hospitality Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) 2016-2022. The research method used is quantitative and descriptive research methods. The population in this study were 203 financial statements from 29 hospitality sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2022. The sampling technique used in this study is a non-probability sampling technique with a purposive sampling approach. Sample count of 70 Financial Statements from 10 Hospitality Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX) 2016-2022. Based on the research results, the determination test of the Cash Turnover variable has no effect of 0.7% on Return On Assets and the Receivables Turnover variable has an effect of 22.3% on Return On Assets. Simultaneously, the Cash Turnover and Receivables Turnover variables have an influence of 20.2% on Return On Assets. Partial research results using the t test, the Cash Turnover variable has no effect on Return On Assets with a significance value of 0.365 > 0.05 and tcount 0.915 < ttable 1.996. The Receivables Turnover variable affects Return On Assets with a significance value of 0.001 <0.05 and tcount 3.571 > ttable 1.996. The results of the study simultaneously using the F test, the Cash Turnover and Receivables Turnover variables affect Return On Assets with a significance value of 0.003 < 0.05 and Fcount 6.561 > Ftable 3.134.